An approach to ecological balance and indigenous knowledge of Alternanthera philoxeroides (Mart.) Griseb in Panikhaiti village of Kamrup (Metropolitan) district of Assam - Sharma, Nandini; Das, Gunamoni (Frontiers in Conservation Science, 2025)
IntroductionThe study examines the ecological and ethnobotanical significance of significance of Alternanthera philoxeroides (Mart) Griseb, commonly known as Alligator weed in Panikhaiti Gaon, a diverse locality in Kamrup Metropolitan district, Assam. The plant often plays a dual role as an ecological invader and a culturally significant species. This study aimed to assess the ecological impact and traditional knowledge associated with A. philoxeroides in the region.MethodsEcological data were collected using the quadrat method (1.5m x 1.5m) with 45 quadrats sampled across three sites. In addition to this, ethnobotanical data were obtained through semi-structured interviews with 45 local informants and supplemented via an online questionnaire. The ecological parameters, Relative Density (RD), Relative Frequency (RF), Relative Dominance (R dom), and Importance Value Index (IVI)—were assessed across these sites.ResultsIn site 1, the RD, RF, R dom, and IVI values were 24.2, 56.1, 45.2, and 125, respectively, while in site 2, they were 45.6, 33.4, 12.8, and 91.8. Site 3 recorded values of 19.3, 33.9, 54.5, and 107.7. Biodiversity indices, including Shannon–Wiener diversity index (H) and Pielou’s evenness index (I), ranged from 0.21 to 0.75 across the sites, indicating variations in species distribution. Beyond its ecological role, A. philoxeroides holds cultural and traditional significance among the local communities. Ethnobotanical findings revealed a range of medicinal and culinary uses for the plant, highlighting its cultural relevance despite its invasive status.DiscussionThe study underscores the value of integrating traditional knowledge with scientific data to inform locally grounded conservation and resource management strategies.